PENGEMBANGAN SISTEM INFORMASI P3M TERINTEGRASI MELALUI REFACTORING DAN PENAMBAHAN FITUR DENGAN METODE R&D - Zulkarnaini; Muhammad Noval; Andre Mariza Putra; Ayu Octarina (LPPM Universitas Abdurrab, 2026)
This study aims to develop an integrated Information System for the Center for Research and Community Service (P3M) at Politeknik Negeri Sriwijaya through the addition of new features and refactoring of the existing system. The previous system suffered from several limitations, including a monolithic architecture, data duplication across modules, and limited flexibility for further development, which negatively affected the efficiency of research and community service management. This study employed the Research and Development (R&D) method, consisting of requirement analysis, system design, prototype development, testing, evaluation, and refinement stages. The results show that the developed system successfully integrates the management of research and community service proposals, reviewer assessment processes, real-time activity monitoring, and automated report generation. Code refactoring improves readability, modularity, and system sustainability. User testing involving administrators, lecturers, and reviewers indicates improvements in administrative efficiency, data accuracy, and user satisfaction. This study contributes to the development of research management information systems in vocational higher education by offering a fully integrated system and a systematic refactoring approach to legacy applications.